Critically important outcomes for infection in trials in kidney transplantation: An international survey of patients, caregivers, and health professionals. Issue 6 (11th April 2022) - Chan, Samuel; Howell, Martin; Johnson, David W.; Hawley, Carmel M.; Tong, Allison; Craig, Jonathan C.; Cao, Christopher; Blumberg, Emily; Brennan, Daniel; Campbell, Scott B.; Francis, Ross S.; Huuskes, Brooke M.; et al.
Abstract: Background: Infections are a common complication following kidney transplantation, but are reported inconsistently in clinical trials. This study aimed to identify the infection outcomes of highest priority for patients/caregivers and health professionals to inform a core outcome set to be reported in all kidney transplant clinical trials. Methods: In an international online survey, participants rated the absolute importance of 16 infections and eight severity dimensions on 9‐point Likert Scales, with 7–9 being critically important. Relative importance was determined using a best–worst scale. Means and proportions of the Likert‐scale ratings and best–worst preference scores were calculated. Results: 353 healthcare professionals (19 who identified as both patients/caregiver and healthcare professionals) and 220 patients/caregivers (190 patients, 22 caregivers, eight who identified as both) from 55 countries completed the survey. Both healthcare professionals and patients/caregivers rated bloodstream (mean 8.4 and 8.5, respectively; aggregate 8.5), kidney/bladder (mean 7.9 and 8.4; aggregate 8.1), and BK virus (mean 8.1 and 8.6; aggregate 8.3) as the top three most critically important infection outcomes, whilst infectious death (mean 8.8 and 8.6; aggregate 8.7), impaired graft function (mean 8.4 and 8.7; aggregate 8.5) and admission to the intensive care unit (mean 8.2 and 8.3; aggregate 8.2) were the top three severity dimensions. Relative importance (best–worst) scores were consistent. Conclusions: Healthcare professionals and patients/caregivers consistently identified bloodstream infection, kidney/bladder infections, and BK virus as the three most important infection outcomes, and infectious death, admission to intensive care unit and infection impairing graft function as the three most important infection severity outcomes.